2014
DOI: 10.1093/jhered/esu052
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Horizontal Gene Transfer in Cotton Plants

Abstract: Plant mitochondrial and chloroplast genes that underwent horizontal transfer have been identified by parasite and grafting systems, respectively. Here, we directly observed 3 horizontal gene transfer (HGT) events in the 45 second axillary shoots of grafted cotton plants (Gossypium barbadense and Gossypium hirsutum) after extirpating the first axillary bud. The second axillary shoots showed phenotypic variations in cotton flowers and seeds that were evidence of spontaneous development from cells in the grafting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
2
5
0
1
Order By: Relevance
“…It is accepted that grafting does not alter the genetic content of the graft partners and their offspring. However, there are considerable amount of studies reported the DNA alteration due to grafting 9 , 30 34 . Previous studies also showed that genetic material could be transported via plasmodesmata between stock and scion cells in interspecific graft junction zones between different Nicotiana species 35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is accepted that grafting does not alter the genetic content of the graft partners and their offspring. However, there are considerable amount of studies reported the DNA alteration due to grafting 9 , 30 34 . Previous studies also showed that genetic material could be transported via plasmodesmata between stock and scion cells in interspecific graft junction zones between different Nicotiana species 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Grafting approaches reported here could be used in cotton improvement studies. For instance, interspecific grafting experiments would allow the increase in some physiologic, agronomic, genetic and epigenetic traits 34 , 42 . Grafting experiments have been already used in cotton for different purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer taraftan hem meyve hem de sebze türleri arasında çok uzun süreden beri geleneksel olarak yapılan aşılama uygulamaları bitkiden bitkiye doğal yollarla gerçekleşen ve hücresel teması gerektiren YGT'nin diğer bir örneğini oluşturmaktadır. Temelinde dayanıklı uzak akraba türler ile ticari çeşitler arasında gerçekleştirilen bu uygulamalarda doğrudan hücresel temasın bir sonucu olarak genomik, organel DNA parçaları ya da transkripsiyon ürünlerinin (mRNA, RNAi) hücreler arasındaki mikroskobik boşluklar (plasmodesmata channel) ve mikrokesecikler yolu ile karşılıklı paylaşıldığı belirlenmiştir [64,65]. Ancak güncel literatür bilgileri özellikle söz konusu YGT'ne yönelik geçişlerin sadece aşı bölgesindeki hücreler ile sınırlı olduğunu, bu taşınımların apikal meristem hücrelerine ve dolayısıyla çiçek tomurcuklarındaki generatif hücrelere ulaşmadığı ve bu nedenle sonraki döllere aktarılmadıklarını göstermiştir [66].…”
Section: Bitkilerde Doğal Yollarla Meydana Gelen Dikey Ve Yatay Gen Transferleriunclassified
“…Natural grafting may enable HGT between two plants [9,15]. In a recent study, three HGT events were observed on axillary shoots of grafted cotton plants, but the genetic variations were not stably inherited across three generations [75]. Two research groups recreated HGT by grafting two lines or species of tobacco and found that nuclear genomes, entire chloroplasts and organellar DNA travelled across the graft junction through plasmodesmata [71,[76][77][78].…”
Section: Mechanisms Of Hgt Among Plantsmentioning
confidence: 99%